Bjr,
a) 5x - 2 = -7
⇒ 5x = -7+2 = -5
⇒ x = -5 ÷ 5 = -1
b) 9x -64 = -1
⇒ 9x = -1 + 64 = 63
⇒ x = 63 ÷ 9 = 7
c) 3x + 2 = x + 6
⇒ 3x - x = 6 - 2
⇒ 2x = 4
⇒ x = 4 ÷ 2 = 2
d) -8x + 3 = 5x - 2
⇒ -8x - 5x = -2 - 3 = -5
⇒ -13x = -5
⇒ x = (-5) ÷ (-13) = 5/13
e) 4 - (3x + 1) = 3(x+5)
⇒ 4 - 3x - 1 = 3x + 15
⇒ -3x - 3x = 15 - 4 + 1 = 12
⇒ -6x = 12
⇒ x = 12 ÷ (-6) = -2
f) 2(x - 3) = 4 + (x - 1)
⇒ 2x - 6 = 4 + x - 1
⇒ 2x - x = 4 - 1 + 6 = 9
⇒ x = 9
g) 2x/5 - 1/10 = 1/2
⇒ 2x/5 = 1/2 + 1/10 = 6/10
⇒ 2x = 6/10 × 5 = 30/10 = 3
⇒ x = 3/2
h) 2/5 - x/3 = 4x + (-1/15)
⇒ -x/3 - 4x = -1/15 - 2/5
⇒ -x/3 - 12x/3 = -1/15 - 6/15
⇒ -13x/3 = -7/15
⇒ -13x = (-7/15) × 3 = -21/15 =
⇒ x = (-21/15) ÷ (-13) = 21/195 = 7/65